The complete mitochondrial genome of the North Chinese Leopard (Panthera pardus japonensis). (3rd March 2016) - Dou, Hailong; Feng, Limin; Xiao, Wenhong; Wang, Tianming
Abstract: The North Chinese Leopard ( Panthera pardus japonensis) is an endemic subspecies of Panthera pardus to China, living in small and isolated populations with a severely fragmented distribution. Here we first sequenced and annotated its complete mitochondrial genome. The total length of the North Chinese Leopard is of 16, 966 base pairs that consist of 2 rRNA gene, 22 tRNA genes, 13 protein-coding genes, 1 OL R and 1 control region (CR). The structures of the genomes were highly similar to other Felidae.